IMPLEMENTASI PEMBELAJARAN TEMATIK BERBASIS SISTEM AMONG DI SEKOLAH DASAR KECAMATAN JAWAI SAMBAS - Irsa Marisa; Masudi Masudi; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThematic learning is a teaching strategy that involves themes to create active, meaningful, and attractive learning for students in primary schools. This study aims to describe and determine the implementation of thematic learning conducted by the teacher by applying the among system. This research was conducted at SDN 06 Pelimpaan and SDN 17 Sarang Burung Kuala, Jawai District. Sambas. The subjects in this study were teachers and students in grade IV. Data collection was carried out by observing, interviewing and documenting. Data analysis was carried out in stages: data collection, data reduction, data display, and drawing conclusions. The technique of checking the validity of the data used triangulation. The results of this study indicate that (1) the planning of the among (asih, asah, asuh) system which is integrated in the thematic learning carried out by the teacher is clearly stated in the RPP, (2) The attitude of behavior among which is carried out by the teacher includes: conveying material with great affection, motivating students sincerely, teaching with a smile and friendly, giving attention to students, and good example in actionxx(3) The activities of students in thematic learning based on the system include listening to them. the teacher's explanation in an orderly manner, does not interrupt the teacher's conversation, always works on assignments, and actively questions and answers. (4) The learning outcomes of students are assessed from knowledge, attitudes and skills.Keywords : thematic learning, among system